Evaluation of the Nitrite Test in Screening for Urinary Tract Infection in Febrile Children with Sickle Cell Anaemia. - Brown BJ; Asinobi AO; Fatunde OJ; Osinusi K; Fasina NA (Nigerian Journal of Paediatrics, 2024)
Background: Urinary tract infection (UTI) is a significant cause of morbidity in children and individuals with sickle cell anaemia (SCA) have been reported to be at increased risk. It will be useful to have a simple means of screening such children for UTI with a view to instituting prompt treatment.